2021
DOI: 10.1155/2021/5578216
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Liraglutide on Epicardial Adipose Tissue in Type 2 Diabetes

Abstract: Objective. To study the effect of liraglutide on the thickness of epicardial adipose tissue (EAT) in type 2 diabetes mellitus (T2DM) patients with abdominal obesity. Methods. Abdominal obesity T2DM patients with poor glycemic control were collected and treated with liraglutide. The changes of blood glucose, blood lipid, waist circumference, body mass index (BMI), and EAT thickness were compared after 3 months of treatment with liraglutide. Cardiac magnetic resonance imaging (MRI) was used to measure EAT thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The revision of full-length articles allowed the exclusion of four studies due to irrelevant information in their content. Overall, eighteen studies [21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] enrolling 1064 patients were included in the qualitative and quantitative analyses of the effect of the cardiometabolic drug on EAT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The revision of full-length articles allowed the exclusion of four studies due to irrelevant information in their content. Overall, eighteen studies [21][22][23][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] enrolling 1064 patients were included in the qualitative and quantitative analyses of the effect of the cardiometabolic drug on EAT.…”
Section: Resultsmentioning
confidence: 99%
“…The parasternal long-axis view allowed for the most accurate measurement of EAT on the right ventricle, with optimal cursor beam orientation in each view. The meta-analysis was thus performed on eight studies [21,23,28,29,34,[36][37][38] (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“… 72 However, contradicting these findings, Zhao et al . 73 showed a statistically significant reduction in EAT thickness after 3 months of treatment with liraglutide.…”
Section: Pharmaceutical Clinical Trials Targeting Eatmentioning
confidence: 88%
“…The thickness and volume of EAT in DM patients were significantly thicker than in non-DM patients under the same conditions. 14,15 Moreover, a recent metaanalysis further confirmed the relationship between type 2 diabetes mellitus and EAT, clearly pointing out that the thickness of EAT in diabetic patients is thicker than that in nondiabetic patients. 7 Several studies have shown that taking GLP-1 agonists, 14,16,17 SGLT2-i, 16,18 metformin, 19 and other hypoglycemic drugs and insulin under the skin 20 can reduce the thickness of EAT in patients with type 2 diabetes, which further indicates that EAT is closely related to type 2 diabetes.…”
Section: Epicardial Adipose Tissue and Diabetes Mellitusmentioning
confidence: 94%